(untitled) (Circe de clásicos y modernos, 2018)
Clement of Alexandria is the first Christian philosopher who organizes a system-atic presentation of the concept of the death, a privileged place for anthropology and moral doctrine. In his three major works, Protrepticus, Paedagogus and Stromata, Clement exposes the moral character that involves the concept of θάνατος (death) and its dependence on a key concept of Christian theology, ἁμαρτία(sin). Based on this relation, Clement divides death in three typologies: physical death, death of the soul and gnostic death. In all cases the congregation of Greek and Jewish philosophy favors the understanding of a thanatologiclogic already systematized by the time of the Alexandrian writer.